2023
DOI: 10.21037/jtd-23-284
|View full text |Cite
|
Sign up to set email alerts
|

Agitated saline with 10% blood increases number and stability of microbubbles in detection right-to-left shunt by contrast-enhanced transcranial Doppler: an in vitro and in vivo observational study

Abstract: Background Agitated saline (AS) with blood has been shown to have good tolerance and increased efficacy when used in contrast-enhanced transcranial Doppler (c-TCD) to detect right-to-left shunt (RLS). However, little is known about the effects of blood volume on c-TCD results. Our study investigated the characterization of AS with different blood volumes in vitro and compared the c-TCD results in vivo . Methods In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Recently, an in vitro and in vivo observational study showed that agitated saline with 10% blood increases number and stability of MBs in detection RLS by contrast enhanced transcranial Doppler. And it showed that both the size and number of MBs were most stable in the agitated saline (AS) with 10% blood (10% BAS), which could be the reasons why the 10% BAS had the highest positive rate and RLS levels in cTCD ( 28 ). Our study also showed good repeatability of cTCD with 10% BAS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an in vitro and in vivo observational study showed that agitated saline with 10% blood increases number and stability of MBs in detection RLS by contrast enhanced transcranial Doppler. And it showed that both the size and number of MBs were most stable in the agitated saline (AS) with 10% blood (10% BAS), which could be the reasons why the 10% BAS had the highest positive rate and RLS levels in cTCD ( 28 ). Our study also showed good repeatability of cTCD with 10% BAS.…”
Section: Discussionmentioning
confidence: 99%